EFFECT OF GREEN MARKETING, PRODUCT KNOWLEDGE AND BRAND PERSONALITY ON PURCHASING DECISIONS (STUDY CASE THE BODY SHOP) - Gustiani, Livia G. F.; Jihan, Alma A. N.; Fasya, Salsabila F.; Azzahra, Nadhira R.; Rahmawaty, Jihan P.; Padmakusumah, Rizal R. (CENTRAL ASIA AND THE CAUCASUS, 2022)
Facial and body skin care is the most important thing that everyone pays attention to. With facial and body skin care, you can meet the skin's needs to keep it healthy and nourished. The Body Shop products are one of the well-known brands that contain vegan-based ingredients. This means that all The Body Shop products are free of animal-derived ingredients obtained as a result of slaughtering or hurting animals. Vegetarian products may include basic ingredients of animal-derived products that do not involve slaughter or harm to animals, such as honey, beeswax and lanolin. In this study, the variables studied were green marketing, product knowledge, brand personality and purchasing decisions. Our research is classified as a descriptive study and also uses a verification approach. The purpose of this study is to determine whether there is an influence between green marketing, product knowledge, brand personality on purchasing decisions. Based on the results of the study, it shows that green marketing and brand personality have a positive and partial effect on Purchasing Decisions for The Body Shop products, while Product Knowledge has no positive and partially significant effect on Purchasing Decisions for The Body Shop products.